PENGARUH DISKON PADA MARKETPLACE SHOPEE TERHADAP PERILAKU KONSUMTIF PADA MASYARAKAT PRABUMULIH TIMUR - ernawati erna (LA RIBA: Jurnal Perbankan Syariah, 2024)
This study aims to determine the effect of discounts on the Shopee marketplace on the consumptive behavior of the community in Prabumulih Timur District. The research employs a quantitative method with a sample of 100 respondents, selected using the quota sampling technique. The data analysis method used is simple linear regression to examine the extent of the influence of discounts on the Shopee marketplace on the consumptive behavior of the community in Prabumulih Timur District. Based on the results of the simple linear regression analysis conducted in this study, the t-test results show that tcount=11.288t_{count}=11.288tcount???=11.288 > ttable=1.660t_{table} = 1.660ttable???=1.660. Thus, it can be concluded that discounts on the Shopee marketplace have a positive effect on the consumptive behavior of the community in Prabumulih Timur District